[Laiškas] / Dobrianskis Flavijonas - Tadui Vrublevskiui. - (:unkn) unknown (My University, 1912)
1 laiškas apie grąžinamą veikalą, rastą tarp jo sūnaus knygų.
Keywords: Rankraščiai; Laiškai; Autografų kolekcija; Vrublevskis, Tadas Stanislovas, 1858-1925; Dobrianskis, Flavijonas